Green Islamic Finance and Digital Economic Resilience in the Indo-Pacific Region - Lucky Nugroho; Ibrahim Musa Gani; Harnovinsah; Baihaki Abdullah; Mahroji (Lembaga Ketahanan Nasional Republik Indonesia, 2025)
Purpose: This study comparatively analyses geoeconomic strategies for advancing green Islamic finance and digital economic resilience in the Indo-Pacific region through the integration of Islamic economics, sustainability, and digital transformation to strengthen national resilience from an Asta Gatra perspective. Study Design/Methodology/Approach: This study uses a descriptive qualitative approach with content and thematic analysis based on Tawhid String Relation Theory (TSR) and Absorptive Capacity Theory (ACT) to explain the adaptation of Islamic finance to technological, environmental, and geopolitical changes. Data were collected from peer-reviewed journal articles, policy documents, institutional reports, and relevant literature on Islamic finance, green finance, digital transformation, and Indo-Pacific resilience. Findings: The findings show that Islamic finance demonstrates strong conceptual alignment with sustainability and digital ethics; however, implementation gaps remain in policy coherence, digital infrastructure, and human resource readiness. The study identifies three key enablers for effective integration: ESG-orientated Sharia financial instruments, Sharia-compliant digital solutions, and value-driven strategic alignment at the organisational level. A conceptual framework is proposed linking maqasid al-Shari’ah, particularly hifz al-mal and hifz al-bi’ah, with digital inclusion and environmental stewardship to strengthen economic and environmental resilience in the Indo-Pacific within the Asta Gatra framework. Originality/Value: This study offers an integrative framework that consolidates Islamic finance, sustainability, and the digital economy into a unified strategic approach. It extends the applied scope of Tawhid String Relation and Absorptive Capacity Theory and provides practical insights for strengthening Islamic financial development, digital transformation, and sustainability-orientated national resilience.